A Lectin Receptor-Like Kinase Mediates Pattern-Triggered Salicylic Acid Signaling. Issue 4 (10th July 2017) - Luo, Xuming; Xu, Ning; Huang, Junkai; Gao, Feng; Zou, Huasong; Boudsocq, Marie; Coaker, Gitta; Liu, Jun
Abstract : The Arabidopsis L-type lectin receptor-like kinase LecRK-IX.2 recruits calcium dependent protein kinases (CPKs) to phosphorylate NADPH oxidase RbohD to activate H2O2-SA circuit. Abstract: Plant surface-localized pathogen recognition receptors (PRR s) perceive conserved microbial features, termed pathogen-associated molecular patterns (PAMPs), resulting in disease resistance. PAMP perception leads to calcium influx, MAPK activation, a burst of reactive oxygen species (ROS ) mediated by RbohD, accumulation of the defense hormone salicylic acid (SA ), and callose deposition. Lectin receptor-like kinases (LecRKs) belong to a specific PRR family and are important players in plant innate immunity. Here, we report that LecRK-IX.2 is a positive regulator of PRR -triggered immunity. Pathogen infection activated the transcription of Arabidopsis ( Arabidopsis thaliana ) LecRK-IX.2, and the LecRK-IX.2 knockout lines exhibited enhanced susceptibility to virulent Pseudomonas syringae pv tomato DC3000. In addition, LecRK-IX.2 is capable of inducing RbohD phosphorylation, likely by recruiting calcium-dependent protein kinases to trigger ROS production in Arabidopsis. Overexpression of LecRK-IX.2 resulted in elevated ROS and SA and enhanced systemic acquired resistance to P. syringae pv tomato DC3000. Our data highlight the importance of LecRKs in plant immune signaling and SA accumulation.